Navier-Stokes/darcy coupling: modeling, analysis, and numerical approximation - Discacciati, Marco; Quarteroni, Alfio (Revista Matemática Complutense, 2009)
This pap er is an overview of known and new results ab out the coupling of Navier-Stokes and Darcy equations to model the filtration of incompressible fluids through p orous media. We discuss coupling conditions and we analyze the global coupled model in order to prove its well-p osedness and to characterize effective algorithms to compute the solution of its numerical approximation.